Increasing Literacy and Numeracy and Adapting Technology Through the Campus Teaching Program - Bela, Maria Editha; Coo, Petronela; Bhoke, Wilibaldus; Hari, Christina Lusiana (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research aims to determine the increase in students' literacy and numeracy skills. With a population of SD Inpres Rawe students and as a sample, namely fifth grade students at SD Inpres Rawe. The method used in this program is an interactive and participatory approach. The final results of the Teaching Campus program were significantly able to improve the literacy and numeracy skills of students at SD Inpres Rawe. After this program was implemented for four months, there was an increase in the average literacy score by 85% and the average numeracy score by 65% based on the pretest and posttest results. This program provides an opportunity for students to make a positive contribution to basic education, while students benefit from a learning approach that is innovative, interactive and focused on improving literacy and numeracy.